CRISPR-Cas: To take up DNA or not, that is the question - Weinberger, Ariel D. (2012)
Historically landmark experiments showed that capsule switching is critical for Streptococcus pneumonia survival. Further studies demonstrated that capsule ‘transformation’ occurs via DNA uptake. In this issue of Cell Host and Microbe, Bikard et al. (2012) show that CRISPR-Cas systems inhibit DNA uptake, selecting for the outgrowth of CRISPR-defective pneumococci.